There Are Two Poles, One Each on Either Bank of a River Just Opposite to Each Other. One Pole is 60 M High. from the Top of this Pole, the Angle of Depression of the Top And. - Mathematics

Advertisements
Advertisements
Sum

There are two poles, one each on either bank of a river just opposite to each other. One pole is 60 m high. From the top of this pole, the angle of depression of the top and foot of the other pole are 30° and 60° respectively. Find the width of the river and height of the other pole.

Advertisements

Solution


Let the width of the river be w.
In ΔABC,
tan 60° = `"AB"/"BC"`

⇒ `sqrt3` = `60/w`

⇒ w = `60/(sqrt3) = (60sqrt3)/3= 20sqrt3`
In △AED,
tan30° = `"AE"/"ED"`

⇒ `1/(sqrt3) = "AE"/w`

⇒ `1/(sqrt3) = "AE"/(20sqrt3)`

⇒ AE = 20
Height of pole CD = AB − AE
= 60 − 20 = 40 m.
Thus, width of river is `20sqrt3` = 20 x 1.732 = 34.64 m
Height of pole = 40 m.

  Is there an error in this question or solution?
2018-2019 (March) 30/4/3

RELATED QUESTIONS

If tanθ + sinθ = m and tanθ – sinθ = n, show that `m^2 – n^2 = 4\sqrt{mn}.`


9 sec2 A − 9 tan2 A = ______.


Prove the following identities, where the angles involved are acute angles for which the expressions are defined:

`(tan theta)/(1-cot theta) + (cot theta)/(1-tan theta) = 1+secthetacosectheta`

[Hint: Write the expression in terms of sinθ and cosθ]


Prove the following identities, where the angles involved are acute angles for which the expressions are defined.

`(sintheta - 2sin^3theta)/(2costheta - costheta) =tan theta`

 


Evaluate without using trigonometric tables:

`cos^2 26^@ + cos 64^@ sin 26^@ + (tan 36^@)/(cot 54^@)`


Prove the following trigonometric identities.

sec A (1 − sin A) (sec A + tan A) = 1


Prove the following trigonometric identities.

`cot^2 A cosec^2B - cot^2 B cosec^2 A = cot^2 A - cot^2 B`


Prove the following trigonometric identities.

tan2 A sec2 B − sec2 A tan2 B = tan2 A − tan2 B


Prove.
`1/(1+cosA)+1/(1-cosA)=2cosec^2A`


If x = r cos A cos B, y = r cos A sin B and Z = r sin A, show that:
x2 + y2 + z2 = r2


Prove that

`1/(sinA-cosA)-1/(sinA+cosA)=(2cosA)/(2sin^2A-1)`


`sin^2 theta + cos^4 theta = cos^2 theta + sin^4 theta`


`((sin A-  sin B ))/(( cos A + cos B ))+ (( cos A - cos B ))/(( sinA + sin B ))=0` 


If `( cosec theta + cot theta ) =m and ( cosec theta - cot theta ) = n, ` show that mn = 1.


If `( cos theta + sin theta) = sqrt(2) sin theta , " prove that " ( sin theta - cos theta ) = sqrt(2) cos theta`


Write the value of `3 cot^2 theta - 3 cosec^2 theta.`


If `sin theta = x , " write the value of cot "theta .`


Prove that:

`(sin^2θ)/(cosθ) + cosθ = secθ`


Prove that `(sinθ - cosθ + 1)/(sinθ + cosθ - 1) = 1/(secθ - tanθ)`


If sec2 θ (1 + sin θ) (1 − sin θ) = k, then find the value of k.


If cosec2 θ (1 + cos θ) (1 − cos θ) = λ, then find the value of λ. 


cos4 A − sin4 A is equal to ______.


\[\frac{\tan \theta}{\sec \theta - 1} + \frac{\tan \theta}{\sec \theta + 1}\] is equal to 

 

 


Prove the following identity :

cosecθ(1 + cosθ)(cosecθ - cotθ) = 1


Prove the following identity :

`(1 - tanA)^2 + (1 + tanA)^2 = 2sec^2A`


Prove the following identity : 

`1/(sinA + cosA) + 1/(sinA - cosA) = (2sinA)/(1 - 2cos^2A)`


If `x/(a cosθ) = y/(b sinθ)   "and"  (ax)/cosθ - (by)/sinθ = a^2 - b^2 , "prove that"  x^2/a^2 + y^2/b^2 = 1`


Prove that `sinA/sin(90^circ - A) + cosA/cos(90^circ - A) = sec(90^circ - A) cosec(90^circ - A)`


If x = r sin θ cos Φ, y = r sin θ sin Φ and z = r cos θ, prove that x2 + y2 + z2 = r2


Prove the following identities.

`costheta/(1 + sintheta)` = sec θ – tan θ


Prove the following identities.

sec6 θ = tan6 θ + 3 tan2 θ sec2 θ + 1


Prove the following identities.

`(cot theta - cos theta)/(cot theta + cos theta) = ("cosec"  theta - 1)/("cosec"  theta + 1)`


Prove the following identities.

`(sin^3"A" + cos^3"A")/(sin"A" + cos"A") + (sin^3"A" - cos^3"A")/(sin"A" - cos"A")` = 2


If cot θ + tan θ = x and sec θ – cos θ = y, then prove that `(x^2y)^(2/3) – (xy^2)^(2/3)` = 1


If `cos theta/(1 + sin theta) = 1/"a"`, then prove that `("a"^2 - 1)/("a"^2 + 1)` = sin θ


tan θ cosec2 θ – tan θ is equal to


Prove that `cot^2 "A" [(sec "A" - 1)/(1 + sin "A")] + sec^2 "A" [(sin"A" - 1)/(1 + sec"A")]` = 0


Prove that `(tan^2 theta - 1)/(tan^2 theta + 1)` = 1 – 2 cos2θ


If a cos θ – b sin θ = c, then prove that (a sin θ + b cos θ) = `±  sqrt("a"^2 + "b"^2 -"c"^2)`


If sin θ + sin2 θ = 1 show that: cos2 θ + cos4 θ = 1


Choose the correct alternative:

cos θ. sec θ = ?


Choose the correct alternative:

tan (90 – θ) = ?


If tan θ = `13/12`, then cot θ = ?


Prove that cos2θ . (1 + tan2θ) = 1. Complete the activity given below.

Activity:

L.H.S = `square`

= `cos^2theta xx square    .....[1 + tan^2theta = square]`

= `(cos theta xx square)^2`

= 12

= 1

= R.H.S


`5/(sin^2theta) - 5cot^2theta`, complete the activity given below.

Activity:

`5/(sin^2theta) - 5cot^2theta`

= `square (1/(sin^2theta) - cot^2theta)`

= `5(square - cot^2theta)   ......[1/(sin^2theta) = square]`

= 5(1)

= `square`


If 3 sin θ = 4 cos θ, then sec θ = ?


Prove that sec2θ − cos2θ = tan2θ + sin2θ


Prove that `(cos^2theta)/(sintheta) + sintheta` = cosec θ


tan2θ – sin2θ = tan2θ × sin2θ. For proof of this complete the activity given below.

Activity:

L.H.S = `square`

= `square (1 - (sin^2theta)/(tan^2theta))`

= `tan^2theta (1 - square/((sin^2theta)/(cos^2theta)))`

= `tan^2theta (1 - (sin^2theta)/1 xx (cos^2theta)/square)`

= `tan^2theta (1 - square)`

= `tan^2theta xx square`    .....[1 – cos2θ = sin2θ]

= R.H.S


If sec θ = `41/40`, then find values of sin θ, cot θ, cosec θ


Prove that `(1 + sintheta)/(1 - sin theta)` = (sec θ + tan θ)2 


Prove that

`(cot "A" + "cosec  A" - 1)/(cot"A" - "cosec  A" + 1) = (1 + cos "A")/"sin A"`


If 3 sin A + 5 cos A = 5, then show that 5 sin A – 3 cos A = ± 3


Show that tan 7° × tan 23° × tan 60° × tan 67° × tan 83° = `sqrt(3)`


If sin θ + cos θ = `sqrt(3)`, then show that tan θ + cot θ = 1


Simplify (1 + tan2θ)(1 – sinθ)(1 + sinθ)


Complete the following activity to prove:

cotθ + tanθ = cosecθ × secθ

Activity: L.H.S. = cotθ + tanθ

= `cosθ/sinθ + square/cosθ`

= `(square + sin^2theta)/(sinθ xx cosθ)`

= `1/(sinθ xx  cosθ)` ....... ∵ `square`

= `1/sinθ xx 1/cosθ`

= `square xx secθ`

∴ L.H.S. = R.H.S.


Let x1, x2, x3 be the solutions of `tan^-1((2x + 1)/(x + 1)) + tan^-1((2x - 1)/(x - 1))` = 2tan–1(x + 1) where x1 < x2 < x3 then 2x1 + x2 + x32 is equal to ______.


If 2 cos θ + sin θ = `1(θ ≠ π/2)`, then 7 cos θ + 6 sin θ is equal to ______.


Let α, β be such that π < α – β < 3π. If sin α + sin β = `-21/65` and cos α + cos β = `-27/65`, then the value of `cos  (α - β)/2` is ______.


Show that, cotθ + tanθ = cosecθ × secθ

Solution :

L.H.S. = cotθ + tanθ

= `cosθ/sinθ + sinθ/cosθ`

= `(square + square)/(sinθ xx cosθ)`

= `1/(sinθ xx cosθ)` ............... `square`

= `1/sinθ xx 1/square`

= cosecθ × secθ

L.H.S. = R.H.S

∴ cotθ + tanθ = cosecθ × secθ


sec θ when expressed in term of cot θ, is equal to ______.


Prove that `(1 + tan^2 A)/(1 + cot^2 A)` = sec2 A – 1


Share
Notifications



      Forgot password?
Use app×